Outcomes after sofosbuvir-containing regimens for hepatitis C virus in patients with decompensated cirrhosis: a real-world study - Fanpu Ji; Wenjun Wang; Shuangsuo Dang; Shengbang Wang; Burong Li; Dan Bai; Wenxue Zhao; Hong Deng; Changyin Tian; Zongfang Li (Infectious Agents and Cancer, 2017)
Abstract Background Direct-acting antivirals have been used for decompensated cirrhotic patients with hepatitis C virus (HCV) infection. However, the benefits in Chinese patients with decompensated cirrhosis are unclear. Methods Thirty patients with HCV infection and decompensated cirrhosis were administered sofosbuvir-containing regimens at our hospital between April and December 2015. The efficacy and safety of the treatments was determined by sustained virological response at week 12 (SVR 12), change of liver function and adverse events. Results The cohort included 13 treatment-experienced and 17 treatment-naïve patients. A total of 27 patients (90%) achieved SVR 12. No baseline characteristics (sex, age, treatment-experience, genotype, viral load, liver function or splenectomy) was association with achievement of SVR 12. Patients achieved SVR 12 had significantly improved liver function by post-treatment week 12 (P < 0.05). Of the 30 patients, six developed anemia, one developed hepatic decompensation, two developed impaired renal function and one developed a severe upper respiratory tract infection during the treatment. There was no death or HCC development during 12 months of follow-up off-therapy. Two patients (7.4%) with SVR 12 experienced new decompensated episodes during the follow-up. Conclusion Sofosbuvir-containing regimens are effective in Chinese HCV patients with decompensated cirrhosis, regardless of baseline characteristics, as demonstrated by a high rate of SVR 12, as well as improvement in liver function. Although antiviral therapy is generally well tolerated, a vigilant monitoring of anemia and renal function should be mandatory.